Hydrocarbon and Petroleum with SETS Approach Module to Train Students’ Critical Thinking Skills - Putri, Dinda Karunia; Rusmini, Rusmini (Universitas Islam Negeri Raden Intan Lampung, 2021)
The aim of this study was to develop a module with the Science, Environment, Technology and Society (SETS) approach to train critical thinking skills on hydrocarbons and petroleum using the Research and Development (R and D) method. This development modul was validated by 3 experts, while the limited trial was only limited to a small trial with 3 respondents from class XII students of SMAN 10 Surabaya to obtain practical and effective data of modules that developed on a small scale. This experiment obtained expert validation results 87% with the “very valid” category, module practicality 94% with the “very practical” category and module effectiveness of 0.8 with the “high” category. The effectiveness of the module is obtained from the pretest and posttest that 3 students have increased their critical thinking skills after the module is given. Based on this study, it can be concluded that the module with the SETS approach in the material of hydrocarbons and petroleum can train students’ critical thinking skills and it is feasible to be tested on larger respondents.